Odyssey-VCS a flexible version control system for UML model elements. - Oliveira, Hamilton
Many current version control systems use a simple data model that is barely sufficient to manipulate source-code. This simple data model is not sufficient to provide versioning capabilities for software modeling environments, which are strongly focused on analysis and architectural design artifacts. In this work, we introduce a flexible version control system for UML model elements. This version control system, named Odyssey-VCS, deals with the complex data model used by UML-based CASE tools. Moreover, it allows the configuration of both the unit of versioning and unit of comparison for each specific project, respecting the different needs of the diverse development scenarios.